Objective Feedback: The Views of Pedagogical Study Programme Students - Stramkale, Ligita (Journal of Education Culture and Society, 2024)
Aim. The study aims to determine the views of the pedagogical study programme students about providing objective feedback in the educational process to identify its main characteristics.Methods. The study uses a mixed research design through the collection and analysis of quantitative and qualitative data within the framework of one study. The study included 82 (n=82) participants studying in part-time bachelor’s and master’s study programmes. The study addresses three research questions: RQ1: At what level do students assess the statements describing the provision of objective feedback? RQ2: What is the difference in students’ views about objective feedback based on the study programme level and their employment? RQ3: What are the main characteristics of objective feedback? SPSS version 22 was used for quantitative data analysis, but the qualitative data were processed using content analysis. Results. Most respondents agree that objective feedback is significant and motivates students to learn. The study identifies nine main characteristics of objective feedback that were divided into three groups: teacher personality traits, teaching and learning outcomes, and teacher professionalism. The study found that those students who, in parallel with their studies, work part-time in one of the general education institutions rate the competence of teachers in providing objective feedback statistically significantly higher than those students who work in a profession outside the education system or do not work at all. Conclusion. The findings provide a better understanding of the main characteristics of objective feedback, thereby reducing the subjectivity in assessment.